Membrane Heterogeneity Controls Cellular Endocytic Trafficking - Redpath, Gregory M. I.; Betzler, Verena M.; Rossatti, Pascal; Rossy, Jérémie (Frontiers in Cell and Developmental Biology, 2020)
Endocytic trafficking relies on highly localised events in cell membranes. Endocytosis involves the gathering of protein (cargo/receptor) at distinct plasma membrane locations defined by specific lipid and protein compositions. Simultaneously, the molecular machinery that drives invagination and eventually scission of the endocytic vesicle assembles at the very same place on the inner leaflet of the membrane. It is membrane heterogeneity – the existence of specific lipid and protein domains in localised regions of membranes – that creates the distinct molecular identity required for an endocytic event to occur precisely when and where it is required rather than at some random location within the plasma membrane. Accumulating evidence leads us to believe that the trafficking fate of internalised proteins is sealed following endocytosis, as this distinct membrane identity is preserved through the endocytic pathway, upon fusion of endocytic vesicles with early and sorting endosomes. In fact, just like at the plasma membrane, multiple domains coexist at the surface of these endosomes, regulating local membrane tubulation, fission and sorting to recycling pathways or to the trans-Golgi network via late endosomes. From here, membrane heterogeneity ensures that fusion events between intracellular vesicles and larger compartments are spatially regulated to promote the transport of cargoes to their intracellular destination.